A comprehensive thermal assessment of dry cooled supercritical CO2 power cycles. (5th February 2020) - Monjurul Ehsan, M.; Duniam, Sam; Li, Jishun; Guan, Zhiqiang; Gurgenci, Hal; Klimenko, Alexander
Highlights: NDDCT is designed for the recompression and partial cooling sCO2 cycles. Optimum operating conditions are rectified prior to the modelling of NDDCT. An iterative method for modelling the finned tube heat exchanger unit is used. Impact of ambient temperature is investigated on the cycle performance. A comparative study between the recompression and partial cooling cycle. Abstract: In arid areas, dry cooling technology is a preferable alternate of wet cooling mainly owing to the scarcity of abundant water supply. However, the supercritical CO2 power cycle still offers considerable thermal performance even at higher ambient temperature using dry cooling. The novelty of this work is the exhaustive designing of dry cooler for supercritical CO2 cycles (recompression and partial cooling) in concentrating solar power application. Prior to the design of tower, a preliminary analysis is conducted in achieving the optimum main compressor inlet temperature (33 °C-recompression and 40 °C-partial cooling) at which the cycle delivers the maximal efficiency. The comparison is performed at same higher and lower pressure and for the partial cooling, the intermediate pressure is optimized. At relatively higher compressor inlet temperatures (above 50 °C), the partial cooling achieves higher efficiency while at lower temperatures (30–49 °C), the recompression shows superior performance. An iterative nodal method is used for the air-cooled finned tube heat exchanger units that takes account of the dramatic variation in thermodynamic properties of CO2 with the bulk temperature. Kroger's detailed methodology of designing dry cooler is adapted with the implementation of nodal approach for CO2 property variation. A dry cooling tower with 52.45 m height is essential for the recompression cycle, whereas the partial cooling requires two towers of the height of 35.4 m and 38.7 m. A thermal assessment is carried out on the dry cooler under various cycle fluid inlet temperatures and ambient temperatures. During hot and humid ambient conditions, lower compressor inlet temperatures (up to 53.1 °C) are obtained with the recompression cycle compared to partial cooling (up to 64.5 °C). In extreme climate condition of 50 °C air temperature, the recompression cycle provides superior thermal efficiency (46.5% against 45.5%). For future commercialization of dry cooled sCO2 power plant, the recompression cycle is preferred due to its superior performance and lower capital cost for cooling tower design and solar field. The work demonstrates the impact of dry cooling tower design strategy in the context of cycle thermal assessment under various working condition.